MENGUNGKAP SEJARAH DAN MOTIF BATIK SEMARANG SERTA PENGARUH TERHADAP MASYARAKAT KAMPUNG BATIK TAHUN 1970-1998 - Afreliyanti, Susi (Journal of Indonesian History, 2014)
Kampung Batik Semarang in Rejomulyo Village, District East Semarang. Kampung Batik Batik is the biggest producer in Semarang. In a research report stating that many natives in Semarang livelihood in the batik industry sectors. 1970 - 1998 A lot of events happening in the world of Batik Semarang. From the early generation of batik village until the monetary crisis lunge keeksisan batik dyeing semarang, addition appears also Effect of the batik batik village semarang to society. The results showed that this is the place Kampung Batik largest batik producer disemarang.Tahun 1970 appeared the famous Batik company named "Batikkerij Tan Kong Tin" Which brings many famous motif scene at that time. Seeing that there are motives disemarang visible once the influence of the Dutch, many are calling batik batik semarang as colonial. But at the beginning of production motif dominated chinese descent. In the Year 1997 has been agreed by the General batik international conventions that the process of writing a picture or decoration on any media using wax batik (wax) as a means of printing batik coloring. However, entering 1970 batik production started to decline due to the influx of foreign textile production. Then Batik Semarang suffered a setback in 1998 due to the financial crisis. Masyrakatnya own influence to include three fields, among others, the influence of the Economic, Social and Cultural. Â